1997
DOI: 10.1103/physrevb.55.2701
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling states in vitreousGeO2s

Abstract: Ultrasonic measurements of the attenuation and the velocity variation have been carried out in amorphous GeO 2 at low temperature ͑0.3-10 K͒ and high frequencies ͑80-210 MHz͒. From numerical fits to the tunneling model, the typical parameters of the tunneling states ͑TS͒ were determined and compared to those found for vitreous SiO 2 . The study reveals that in a-GeO 2 , which is considered as a close structural analog to a-SiO 2 , although the density of states is found to be very similar in both materials, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(18 reference statements)
2
4
0
Order By: Relevance
“…The plateau of the 6.3 kHz data [50] in Fig. 5(a) agrees with the tunneling prediction, but the plateau of longitudinal ultrasonic data [51,61] is markedly higher, in agreement with the soft potential calculation. [55], and at 87 kHz [54] in polystyrene with the soft potential calculation (parameters see Table 1).…”
Section: The Crossover From Tunneling To Classical Relaxationsupporting
confidence: 82%
See 1 more Smart Citation
“…The plateau of the 6.3 kHz data [50] in Fig. 5(a) agrees with the tunneling prediction, but the plateau of longitudinal ultrasonic data [51,61] is markedly higher, in agreement with the soft potential calculation. [55], and at 87 kHz [54] in polystyrene with the soft potential calculation (parameters see Table 1).…”
Section: The Crossover From Tunneling To Classical Relaxationsupporting
confidence: 82%
“…Again, the 𝐶 𝑙 -value determined from the 80 MHz sound velocity change in Fig. 5(b), due to unsaturated resonant tunneling at low temperature is only compatible with the measured plateau height in the same sample [51] in the soft potential model, not in the tunneling model. The tunneling model fits yield the same density of states in both measurements, but a markedly stronger coupling constant in the absorption measurement, a result which according to the authors [51] has also been found in ultrasonic measurements of the sound absorption and the sound velocity change of neutron-irradiated quartz [62] and in vitreous silica [63].…”
Section: Fig 8 Comparison Of Measured Low Temperature Sound Absorptio...mentioning
confidence: 65%
“…5. The plateau of the 6.3 kHz data [51] agrees with the tunneling prediction, but the plateau of longitudinal ultrasonic data [52,53] is markedly higher, in agreement with the soft potential calculation. Again, the C l -value determined from the 80 MHz sound velocity change at low temperature [52] is only compatible with the measured plateau height in the soft potential model, not in the tunneling model.…”
Section: A the Crossover From Tunneling To Classical Relaxationsupporting
confidence: 81%
“…the region between the plateau and the loss peak, can arise from incoherent tunnelling effects within the two wells as a consequence of increasing thermal motion which prevents the phase coherence of the TLS tunnelling motion [1]. Limiting the present analysis to the temperature region above 20 K where only the relaxation process is dominant, the loss peak can be described by the asymmetric double-well potential (ADWP) model, following the procedure described by Gilroy and Phillips [14]. Barrier heights V varied randomly over the defect sites with Gaussian distribution,…”
Section: Acoustic Attenuationmentioning
confidence: 99%